1985
DOI: 10.1007/bf01210934
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between DNA repair and cell recovery: Importance of competing biochemical and metabolic processes

Abstract: The relationship between the inhibition of repair of radiation-induced DNA damage and the inhibition of recovery from radiation-induced potentially lethal damage (PLD) by hypertonic treatment was compared in 9L/Ro rat brain tumor cells. Fed plateau phase cultures were gamma-irradiated with 1500 rad and then immediately treated for 20 min with a 37 degree C isotonic (0.15 M) or hypertonic (0.50 M) salt solution. The kinetics of repair of radiation-induced DNA damage as assayed using alkaline filter elution were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It was suggested that perhaps error-prone or error-free repair is predominant in conditions that prevent or promote PLDR, respectively . It has been suggested that imbalances in sets of competing biochemical or metabolic processes postirradiation determines survival rather than the presence of a single class of unrepaired DNA lesions (van Ankeren andWheeler 1985, Wheeler et al . 1992) .…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that perhaps error-prone or error-free repair is predominant in conditions that prevent or promote PLDR, respectively . It has been suggested that imbalances in sets of competing biochemical or metabolic processes postirradiation determines survival rather than the presence of a single class of unrepaired DNA lesions (van Ankeren andWheeler 1985, Wheeler et al . 1992) .…”
Section: Discussionmentioning
confidence: 99%